Diffusion-Weighted MR Imaging Characteristics of an Acute Strokelike Form of Multiple Sclerosis - Rosso, C.; Remy, P.; Creange, A.; Brugieres, P.; Cesaro, P.; Hosseini, H. (American Journal of Neuroradiology, 2006)
SUMMARY: The characteristics of multiple sclerosis (MS) lesions on diffusion-weighted sequences and apparent diffusion coefficient (ADC) mapping at the very early phase of symptoms have not been clearly described. We report the case of a young woman who presented with a sudden pseudostroke form of MS resulting in hemiplegia and sudden aphasia. MR imaging showed a lesion of the left internal capsule with reduced ADC, which suggests an ischemic stroke. This case shows that very acute MS lesions may have reduced ADC on MR imaging, reflecting cytotoxic and not vasogenic edema.